Cold and hot fibrosis define clinically distinct cardiac pathologies - Miyara, Shoval; Adler, Miri; Umansky, Kfir B.; Häußler, Daniel; Bassat, Elad; Divinsky, Yalin; Elkahal, Jacob; Kain, David; Lendengolts, Daria; Ramirez Flores, Ricardo O.; Bueno-Levy, Hanna; Golani, Ofra; et al. (Cell systems, 2025)
Fibrosis remains a major unmet medical need. Simplifying principles are needed to better understand fibrosis and to yield new therapeutic approaches. Fibrosis is driven by myofibroblasts that interact with macrophages. A mathematical cell-circuit model predicts two types of fibrosis: hot fibrosis driven by macrophages and myofibroblasts and cold fibrosis driven by myofibroblasts alone. Testing these concepts in cardiac fibrosis resulting from myocardial infarction (MI) and heart failure (HF), we revealed that acute MI leads to cold fibrosis whereas chronic injury (HF) leads to hot fibrosis. MI-driven cold fibrosis is conserved in pigs and humans. We computationally identified a vulnerability of cold fibrosis: the myofibroblast autocrine growth factor loop. Inhibiting this loop by targeting TIMP1 with neutralizing antibodies reduced myofibroblast proliferation and fibrosis post-MI in mice. Our study demonstrates the utility of the concepts of hot and cold fibrosis and the feasibility of a circuit-to-target approach to pinpoint a treatment strategy that reduces fibrosis. A record of this paper’s transparent peer review process is included in the supplemental information.